Medication time? A User Experience Evaluation of Mobile Applications targeting People with Diabetes - Rodrigues, Maria Elanne M.; Moura, Karla Haryanna S.; Branco, Karina Castelo; Lelli, Valéria; Viana, Windson; Andrade, Rossana M. C.; Santos, Ismayle S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
Diabetes is a chronic disease resulting from a lack of insulin, which permanently alters blood sugar levels. Research by the International Diabetes Federation (IDF) in the year 2021 shows that about 10% of adults aged between 20 and 79 years of the world population live with diabetes. In this context, the use of mobile apps has assisted in monitoring these patients. In this research, the experience of using mobile applications for healthcare patients with diabetes in their daily activities was investigated. For the evaluation, 5 An droid mobile applications were selected for this purpose and 10 participants were invited who were people diagnosed with diabetes. To characterize the target audience, a questionnaire was applied to define the profile of the study participants. Subsequently, each participant chose two apps and followed the script for using the chosen apps. To evaluate the user experience (UX) used the User Experience Questionnaire (UEQ), which assesses aspects of usabil ity (efficiency, perspicuity, and dependability) and user experience (novelty and stimulation). Among the 5 apps evaluated, one of the apps presented problems regarding the stimulus and novelty aspects. The aspect with the lowest Likert scale value among all the apps was a novelty. Thus, the results indicated that most apps present a creative design and an attractive interface according to the users.